1981
DOI: 10.1152/jappl.1981.51.4.830
|View full text |Cite
|
Sign up to set email alerts
|

Importance of inspiratory muscle tone in maintenance of FRC in the newborn

Abstract: The importance of inspiratory muscle tone in the maintenance of functional residual capacity (FRC) in newborns was studied in eight premature infants with birth weights of 1,166 +/- 217 g and gestational age 29 +/- 1.9 wk (mean +/- SD). Rib cage and abdominal anteroposterior diameters were monitored with magnetometers, and electromyograms of the diaphragm and intercostal muscles were recorded with surface electrodes. Sleep state was monitored using electrooculogram and behavioral criteria. We assessed the decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
45
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 0 publications
5
45
1
Order By: Relevance
“…The crying pattern has not been described in earlier reports (7,30,31). All other interrupted expiratory patterns shown in this study were described previously and were considered strategies to defend lung volume (11,12,14,15,(32)(33)(34)(35). We were not able to show a difference in breathing between the groups, except that preterm infants use the expiratory breath hold more often than term infants.…”
Section: Discussionmentioning
confidence: 46%
“…The crying pattern has not been described in earlier reports (7,30,31). All other interrupted expiratory patterns shown in this study were described previously and were considered strategies to defend lung volume (11,12,14,15,(32)(33)(34)(35). We were not able to show a difference in breathing between the groups, except that preterm infants use the expiratory breath hold more often than term infants.…”
Section: Discussionmentioning
confidence: 46%
“…In the adult, the FRC is determined by the elastic recoil forces of the lungs and the chest wall. In the neonate, the end-expiratory lung volume is actively determined by the breathing pattern (1)(2)(3)(4). During apnea, very frequent at this age, the ability to maintain an oxygen supply from the existing reserves will be determined by the size of the FRC, the existence of any underlying disorders affecting lung growth and ongoing changes in lung volume and mechanics.…”
mentioning
confidence: 99%
“…The higher frequency of apneic events commonly observed in active sleep (AS) may be related to a low FRC (2,10), although a decrease in FRC is not always found in this sleep state (7,11). These conflicting results may be explained not only by various FRC measurement techniques but also because breathing regularity (in addition to the potentially differential effects of sleep state) may have affected the data.…”
mentioning
confidence: 99%
“…However, in healthy premature and full-term newborns, it has been demonstrated that electrical activity of the diaphragm, measured with electrodes on the surface of the chest wall, may persist throughout expiration, suggesting a "tonic" activity of the respiratory muscles (1-4). Lopes et al (2) demonstrated that changes in tonic activity of the diaphragm were associated with changes in EELV and provided the original physiologic explanation that persistent diaphragmatic activity during the exhalation period helps to regulate EELV in infants . In healthy full-term or premature infants, the EELV is higher than the relaxation volume, the latter being determined by the passive mechanical properties of the respiratory system (1,3,5).…”
mentioning
confidence: 99%